2020
DOI: 10.3145/epi.2020.jul.03
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in times of pandemics: How online media are starting to treat the economic consequences of the coronavirus crisis

Abstract: Antón-Bravo, Adolfo (2020). "Inequality in times of pandemics: How online media are starting to treat the economic consequences of the coronavirus crisis".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
2
0
3
Order By: Relevance
“…The proposed methodology uses content analysis; although mainly quantitative, it is complemented with value judgements in the form of observations to facilitate the implementation of improvements, in line with that carried out by Odriozola-Chéné et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…The proposed methodology uses content analysis; although mainly quantitative, it is complemented with value judgements in the form of observations to facilitate the implementation of improvements, in line with that carried out by Odriozola-Chéné et al (2020).…”
Section: Methodsmentioning
confidence: 99%
“…In 2020, the articles published in all areas of knowledge had a common denominator: COVID-19. In the case of communication sciences, the studies by Moreno et al (2020), Orduña-Malea et al (2020), Aleixandre-Benavent et al (2020), Odriozola-Chéné et al (2020), Castillo-Esparcia et al (2020), Sales et al (2020) and Ferrer-Sapena et al (2020) have demonstrated how this health crisis, on a global scale, has been a research opportunity for universities around the world. Furthermore, the issue of the coronavirus has improved the dissemination of science, because the scientific community and society have demanded updated information on the pandemic (Cañeles .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Los acontecimientos globales ocurridos en los últimos meses han dibujado un escenario excepcional-mente intenso desde el punto de vista informativo, institucional y político. Hitos como el Brexit y las consecuencias de su acuerdo (Pedrero-Esteban, Pérez-Escoda & Establés, 2021), el flujo migratorio y los refugiados (Rodríguez-Planas y Farré, 2016), la Covid-19 y las consecuencias económicas de esta pandemia (Odriozola-Chéné et al, 2020) o, entre otros, la guerra de Ucrania (Kizilova & Norris, 2022) han incrementado el interés tanto de medios como de ciudadanos por contextualizar el papel que ocupa España en la actualidad europea e internacional, así como en el interés de los agentes políticos e institucionales implicados y la consecuente atribución de responsabilidades (Sánchez Castillo, et al, 2020).…”
Section: Introductionunclassified